• Research
• Open Access

An iterative approach to mixed equilibrium problems and fixed points problems

Fixed Point Theory and Applications20132013:183

https://doi.org/10.1186/1687-1812-2013-183

• Accepted: 28 June 2013
• Published:

Abstract

In the present paper, an iterative algorithm for solving mixed equilibrium problems and fixed points problems has been constructed. It is shown that under some mild conditions, the sequence generated by the presented algorithm converges strongly to the common solution of mixed equilibrium problems and fixed points problems. As an application, we can find the minimum norm element without involving projection.

MSC:47J05, 47J25, 47H09.

Keywords

• mixed equilibrium problem
• fixed point problem
• minimization problem
• strictly pseudo-contractive mapping

1 Introduction

Let H be a real Hilbert space with the inner product $〈\cdot ,\cdot 〉$ and the norm $\parallel \cdot \parallel$, respectively. Let C be a nonempty closed convex subset of H. For a nonlinear mapping $A:C\to H$ and a bifunction $F:C×C\to R$, the mixed equilibrium problem is to find $z\in C$ such that
$F\left(z,y\right)+〈Az,y-z〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C.$
(1.1)
The solution set of (1.1) is denoted by MEP. If $A=0$, then (1.1) reduces to the following equilibrium problem of finding $z\in C$ such that
$F\left(z,y\right)\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C.$
(1.2)
The solution set of (1.2) is denoted by EP. If $F=0$, then (1.1) reduces to the variational inequality problem of finding $z\in C$ such that
$〈Az,y-z〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C.$
(1.3)

The solution set of (1.3) is denoted by VI. Problem (1.1) is very general in the sense that it includes, as special cases, optimization problems, variational inequalities, minimax problems, Nash equilibrium problem in noncooperative games and others. See, e.g., [122].

For solving mixed equilibrium problem (1.1), Moudafi [9] introduced an iterative algorithm and proved a weak convergence theorem. Further, Takahashi and Takahashi [15] introduced the following iterative algorithm for finding an element of $F\left(S\right)\cap \mathit{MEP}$:
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-{x}_{n}〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+S\left({\alpha }_{n}u+\left(1-{\beta }_{n}\right){z}_{n}\right)\hfill \end{array}$
(1.4)

for all $n\ge 0$, where $S:C\to C$ is a nonexpansive mapping. They proved that the sequence $\left\{{x}_{n}\right\}$ generated by (1.4) converges strongly to $z={Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(u\right)$.

Recently, Yao and Shahzad [19] gave the following iteration process for nonexpansive mappings with perturbation: ${x}_{1}\in C$ and
${x}_{n+1}=\left(1-{\beta }_{n}\right){x}_{n}+{\beta }_{n}{Proj}_{C}\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right)T{x}_{n}\right),\phantom{\rule{1em}{0ex}}n\ge 0,$

where $\left\{{\alpha }_{n}\right\}$ and $\left\{{\beta }_{n}\right\}$ are sequences in $\left[0,1\right]$, and the sequence $\left\{{u}_{n}\right\}$ in H is a small perturbation for the n-step iteration satisfying $\parallel {u}_{n}\parallel \to 0$ as $n\to \mathrm{\infty }$. In fact, there are perturbations always occurring in the iterative processes because the manipulations are inaccurate.

Using the ideas in [19], Chuang et al. [4] introduced the following iteration process for finding a common element of the set of solutions of the equilibrium problem and the set of fixed points for a quasi-nonexpansive mapping with perturbation: ${q}_{1}\in H$ and

for all $n\ge 0$. They showed that the sequence $\left\{{q}_{n}\right\}$ converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{EP}}$.

Motivated and inspired by the above works, in the present paper, we construct an iterative algorithm for solving mixed equilibrium problems and fixed points problems. It is shown that under some mild conditions the sequence $\left\{{x}_{n}\right\}$ generated by the presented algorithm converges strongly to the common solution of mixed equilibrium problems and fixed points problems. As an application, we can find the minimum norm element without involving projection.

2 Preliminaries

Let C be a nonempty closed convex subset of a real Hilbert space H. Recall that a mapping $A:C\to H$ is called α-inverse-strongly monotone if there exists a positive real number $\alpha >0$ such that
$〈Ax-Ay,x-y〉\ge \alpha {\parallel Ax-Ay\parallel }^{2},\phantom{\rule{1em}{0ex}}\mathrm{\forall }x,y\in C.$
It is clear that any α-inverse-strongly monotone mapping is monotone and $\frac{1}{\alpha }$-Lipschitz continuous. A mapping $S:C\to C$ is said to be nonexpansive if $\parallel Sx-Sy\parallel \le \parallel x-y\parallel$ for all $x,y\in C$. And a mapping $S:C\to C$ is said to be strictly pseudo-contractive if there exists a constant $0\le \kappa <1$ such that
${\parallel Sx-Sy\parallel }^{2}\le {\parallel x-y\parallel }^{2}+\kappa {\parallel \left(I-S\right)x-\left(I-S\right)y\parallel }^{2},\phantom{\rule{1em}{0ex}}\mathrm{\forall }x,y\in C.$

For such a case, we also say that S is a κ-strictly pseudo-contractive mapping.

Throughout this paper, we assume that a bifunction $F:C×C\to R$ satisfies the following conditions:
1. (H1)

$F\left(x,x\right)=0$ for all $x\in C$;

2. (H2)

F is monotone, i.e., $F\left(x,y\right)+F\left(y,x\right)\le 0$ for all $x,y\in C$;

3. (H3)

for each $x,y,z\in C$, ${lim}_{t↓0}F\left(tz+\left(1-t\right)x,y\right)\le F\left(x,y\right)$;

4. (H4)

for each $x\in C$, $y↦F\left(x,y\right)$ is convex and lower semicontinuous.

We need the following lemmas for proving our main results.

Lemma 2.1 [7]

Let C be a nonempty closed convex subset of a real Hilbert space H. Let $F:C×C\to R$ be a bifunction which satisfies conditions (H1)-(H4). Let $r>0$ and $x\in H$. Then there exists $z\in C$ such that
$F\left(z,y\right)+\frac{1}{r}〈y-z,z-x〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C.$
Further, if ${T}_{r}\left(x\right)=\left\{z\in C:F\left(z,y\right)+\frac{1}{r}〈y-z,z-x〉\ge 0,\mathrm{\forall }y\in C\right\}$, then we have
1. (i)

${T}_{r}$ is single-valued and ${T}_{r}$ is firmly nonexpansive, i.e., for any $x,y\in H$, ${\parallel {T}_{r}x-{T}_{r}y\parallel }^{2}\le 〈{T}_{r}x-{T}_{r}y,x-y〉$;

2. (ii)

EP is closed and convex and $\mathit{EP}=F\left({T}_{r}\right)$.

Lemma 2.2 [19]

Let C, H, F and ${T}_{r}x$ be as in Lemma  2.1. Then we have
${\parallel {T}_{s}x-{T}_{t}x\parallel }^{2}\le \frac{s-t}{s}〈{T}_{s}x-{T}_{t}x,{T}_{s}x-x〉$

for all $s,t>0$ and $x\in H$.

Lemma 2.3 [19]

Let C be a nonempty closed convex subset of a real Hilbert space H. Let the mapping $A:C\to H$ be α-inverse strongly monotone and $r>0$ be a constant. Then we have
${\parallel \left(I-rA\right)x-\left(I-rA\right)y\parallel }^{2}\le {\parallel x-y\parallel }^{2}+r\left(r-2\alpha \right){\parallel Ax-Ay\parallel }^{2},\phantom{\rule{1em}{0ex}}\mathrm{\forall }x,y\in C.$

In particular, if $0\le r\le 2\alpha$, then $I-rA$ is nonexpansive.

Lemma 2.4 [23]

Let $\left\{{x}_{n}\right\}$ and $\left\{{y}_{n}\right\}$ be bounded sequences in a Banach space X and let $\left\{{\beta }_{n}\right\}$ be a sequence in $\left[0,1\right]$ with $0<{lim inf}_{n\to \mathrm{\infty }}{\beta }_{n}\le {lim sup}_{n\to \mathrm{\infty }}{\beta }_{n}<1$. Suppose that ${x}_{n+1}=\left(1-{\beta }_{n}\right){y}_{n}+{\beta }_{n}{x}_{n}$ for all $n\ge 0$ and ${lim sup}_{n\to \mathrm{\infty }}\left(\parallel {y}_{n+1}-{y}_{n}\parallel -\parallel {x}_{n+1}-{x}_{n}\parallel \right)\le 0$. Then ${lim}_{n\to \mathrm{\infty }}\parallel {y}_{n}-{x}_{n}\parallel =0$.

Lemma 2.5 [24]

Let C be a nonempty closed convex subset of a real Hilbert space H. Let $S:C\to C$ be a λ-strict pseudo-contraction. Then we have
1. (i)

$F\left(S\right)=\left\{x:Sx=x\right\}$ is closed convex;

2. (ii)

$\kappa I+\left(1-\kappa \right)S$ for $\kappa \in \left[\lambda ,1\right)$ is nonexpansive.

Lemma 2.6 [25]

Let C be a nonempty closed and convex of a real Hilbert space H. Let $S:C\to C$ be a κ-strictly pseudo-contractive mapping. Then $I-S$ is demi-closed at 0, i.e., if ${x}_{n}⇀x\in C$ and ${x}_{n}-S{x}_{n}\to 0$, then $x=Sx$.

Lemma 2.7 [16]

Assume that $\left\{{a}_{n}\right\}$ is a sequence of nonnegative real numbers such that
${a}_{n+1}\le \left(1-{\gamma }_{n}\right){a}_{n}+{\delta }_{n}{\gamma }_{n},$
where $\left\{{\gamma }_{n}\right\}$ is a sequence in $\left(0,1\right)$ and $\left\{{\delta }_{n}\right\}$ is a sequence such that
1. (1)

${\sum }_{n=1}^{\mathrm{\infty }}{\gamma }_{n}=\mathrm{\infty }$;

2. (2)

${lim sup}_{n\to \mathrm{\infty }}{\delta }_{n}\le 0$ or ${\sum }_{n=1}^{\mathrm{\infty }}|{\delta }_{n}{\gamma }_{n}|<\mathrm{\infty }$.

Then ${lim}_{n\to \mathrm{\infty }}{a}_{n}=0$.

3 Main results

In this section, we prove our main results.

Theorem 3.1 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $A:C\to H$ be an α-inverse-strongly monotone mapping and let $S:C\to C$ be a κ-strictly pseudo-contractive mapping. Suppose that $F\left(S\right)\cap \mathit{MEP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n},\hfill \end{array}$
(3.1)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,2\alpha \right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r1)

${lim}_{n\to \mathrm{\infty }}{u}_{n}=u$ for some $u\in H$;

2. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

3. (r3)

$0 and $\gamma \in \left[\kappa ,1\right)$;

4. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,2\alpha \right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.1) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(u\right)$.

Proof Note that ${z}_{n}$ can be rewritten as ${z}_{n}={T}_{{\lambda }_{n}}\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}\right)$ for each n. Take $z\in F\left(S\right)\cap \mathit{MEP}$. It is obvious that $z={T}_{{\lambda }_{n}}\left(z-{\lambda }_{n}Az\right)={T}_{{\lambda }_{n}}\left({\alpha }_{n}z+\left(1-{\alpha }_{n}\right)\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\right)$ for all $n\ge 0$. By using the nonexpansivity of ${T}_{{\lambda }_{n}}$ and the convexity of $\parallel \cdot \parallel$, we derive
$\begin{array}{c}{\parallel {z}_{n}-z\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}={\parallel {T}_{{\lambda }_{n}}\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}\right)-{T}_{{\lambda }_{n}}\left(z-{\lambda }_{n}Az\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}={\parallel {T}_{{\lambda }_{n}}\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right)\left({x}_{n}-\frac{{\lambda }_{n}A{x}_{n}}{1-{\alpha }_{n}}\right)\right)-{T}_{{\lambda }_{n}}\left({\alpha }_{n}z+\left(1-{\alpha }_{n}\right)\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\parallel \left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right)\left({x}_{n}-\frac{{\lambda }_{n}A{x}_{n}}{1-{\alpha }_{n}}\right)\right)-\left({\alpha }_{n}z+\left(1-{\alpha }_{n}\right)\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}={\parallel \left(1-{\alpha }_{n}\right)\left(\left({x}_{n}-\frac{{\lambda }_{n}A{x}_{n}}{1-{\alpha }_{n}}\right)-\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\right)+{\alpha }_{n}\left({u}_{n}-z\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le \left(1-{\alpha }_{n}\right){\parallel \left({x}_{n}-\frac{{\lambda }_{n}A{x}_{n}}{1-{\alpha }_{n}}\right)-\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}.\hfill \end{array}$
Since A is α-inverse strongly monotone, we know from Lemma 2.3 that
$\begin{array}{c}{\parallel \left({x}_{n}-\frac{{\lambda }_{n}A{x}_{n}}{1-{\alpha }_{n}}\right)-\left(z-\frac{{\lambda }_{n}Az}{1-{\alpha }_{n}}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\parallel {x}_{n}-z\parallel }^{2}+\frac{{\lambda }_{n}\left({\lambda }_{n}-2\left(1-{\alpha }_{n}\right)\alpha \right)}{{\left(1-{\alpha }_{n}\right)}^{2}}{\parallel A{x}_{n}-Az\parallel }^{2}.\hfill \end{array}$
It follows that
$\begin{array}{rcl}{\parallel {z}_{n}-z\parallel }^{2}& \le & \left(1-{\alpha }_{n}\right)\left({\parallel {x}_{n}-z\parallel }^{2}+\frac{{\lambda }_{n}\left({\lambda }_{n}-2\left(1-{\alpha }_{n}\right)\alpha \right)}{{\left(1-{\alpha }_{n}\right)}^{2}}{\parallel A{x}_{n}-Az\parallel }^{2}\right)+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ \le & \left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}.\end{array}$
(3.2)
So, we have
$\begin{array}{rcl}{\parallel {x}_{n+1}-z\parallel }^{2}& =& {\parallel {\beta }_{n}\left({x}_{n}-z\right)+\left(1-{\beta }_{n}\right)\left(\left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}-z\right)\parallel }^{2}\\ \le & {\beta }_{n}{\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel {z}_{n}-z\parallel }^{2}\\ \le & {\beta }_{n}{\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right)\left(\left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\right)\\ =& \left[1-\left(1-{\beta }_{n}\right){\alpha }_{n}\right]{\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ \le & max\left\{{\parallel {x}_{n}-z\parallel }^{2},{\parallel {u}_{n}-z\parallel }^{2}\right\}.\end{array}$

Since ${lim}_{n\to \mathrm{\infty }}{u}_{n}=u$, $\left\{{u}_{n}\right\}$ is bounded. Therefore, by induction, we deduce that $\left\{{x}_{n}\right\}$ is bounded. Hence, $\left\{A{x}_{n}\right\}$, $\left\{{z}_{n}\right\}$ and $\left\{S{z}_{n}\right\}$ are also bounded.

Putting ${y}_{n}={\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}$ for all n, we have
${z}_{n+1}-{z}_{n}={T}_{{\lambda }_{n+1}}{y}_{n+1}-{T}_{{\lambda }_{n+1}}{y}_{n}+{T}_{{\lambda }_{n+1}}{y}_{n}-{T}_{{\lambda }_{n}}{y}_{n}.$
It follows that
$\begin{array}{rcl}\parallel {z}_{n+1}-{z}_{n}\parallel & \le & \parallel {T}_{{\lambda }_{n+1}}{y}_{n+1}-{T}_{{\lambda }_{n+1}}{y}_{n}\parallel +\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \\ \le & \parallel {y}_{n+1}-{y}_{n}\parallel +\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel .\end{array}$
(3.3)
From Lemma 2.3, we know that $I-\lambda A$ is nonexpansive for all $\lambda \in \left(0,2\alpha \right)$. Thus, we have $I-\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}A$ is nonexpansive for all n due to the fact that $\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}\in \left(0,2\alpha \right)$. Then we get
$\begin{array}{rcl}\parallel {y}_{n+1}-{y}_{n}\parallel & =& \parallel {\alpha }_{n+1}{u}_{n+1}+\left(1-{\alpha }_{n+1}\right){x}_{n+1}-{\lambda }_{n+1}A{x}_{n+1}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}\right)\parallel \\ \le & \parallel \left(1-{\alpha }_{n+1}\right)\left({x}_{n+1}-\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}A{x}_{n+1}\right)-\left(1-{\alpha }_{n}\right)\left({x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A{x}_{n}\right)\parallel \\ +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel \\ \le & \left(1-{\alpha }_{n+1}\right)\parallel \left(I-\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}A\right){x}_{n+1}-\left(I-\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}A\right){x}_{n}\parallel \\ +\parallel \left(1-{\alpha }_{n+1}\right)\left({x}_{n}-\frac{{\lambda }_{n+1}}{1-{\alpha }_{n+1}}A{x}_{n}\right)-\left(1-{\alpha }_{n}\right)\left({x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A{x}_{n}\right)\parallel \\ +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel \\ \le & \parallel {x}_{n+1}-{x}_{n}\parallel +|{\alpha }_{n+1}-{\alpha }_{n}|\parallel {x}_{n}\parallel +|{\lambda }_{n+1}-{\lambda }_{n}|\parallel A{x}_{n}\parallel \\ +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel .\end{array}$
(3.4)
By Lemma 2.2, we have
$\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \le \frac{|{\lambda }_{n+1}-{\lambda }_{n}|}{{\lambda }_{n+1}}\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{y}_{n}\parallel .$
(3.5)
From (3.3)-(3.5), we obtain
$\begin{array}{rcl}\parallel {z}_{n+1}-{z}_{n}\parallel & \le & \parallel {x}_{n+1}-{x}_{n}\parallel +|{\alpha }_{n+1}-{\alpha }_{n}|\parallel {x}_{n}\parallel +|{\lambda }_{n+1}-{\lambda }_{n}|\parallel A{x}_{n}\parallel \\ +\frac{|{\lambda }_{n+1}-{\lambda }_{n}|}{{\lambda }_{n+1}}\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{y}_{n}\parallel +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel .\end{array}$
Then
$\begin{array}{c}\parallel \left(\gamma I+\left(1-\gamma \right)S\right){z}_{n+1}-\left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\le \parallel {z}_{n+1}-{z}_{n}\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\le \parallel {x}_{n+1}-{x}_{n}\parallel +|{\alpha }_{n+1}-{\alpha }_{n}|\parallel {x}_{n}\parallel +|{\lambda }_{n+1}-{\lambda }_{n}|\parallel A{x}_{n}\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+\frac{|{\lambda }_{n+1}-{\lambda }_{n}|}{{\lambda }_{n+1}}\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{y}_{n}\parallel +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel .\hfill \end{array}$
Therefore,
$\begin{array}{c}\parallel \left(\gamma I+\left(1-\gamma \right)S\right){z}_{n+1}-\left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}\parallel -\parallel {x}_{n+1}-{x}_{n}\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\le |{\alpha }_{n+1}-{\alpha }_{n}|\parallel {x}_{n}\parallel +|{\lambda }_{n+1}-{\lambda }_{n}|\parallel A{x}_{n}\parallel +{\alpha }_{n+1}\parallel {u}_{n+1}\parallel +{\alpha }_{n}\parallel {u}_{n}\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+\frac{|{\lambda }_{n+1}-{\lambda }_{n}|}{{\lambda }_{n+1}}\parallel {T}_{{\lambda }_{n+1}}{y}_{n}-{y}_{n}\parallel .\hfill \end{array}$
Since ${\alpha }_{n}\to 0$, ${\lambda }_{n+1}-{\lambda }_{n}\to 0$ and ${lim inf}_{n\to \mathrm{\infty }}{\lambda }_{n}>0$, we obtain
$\underset{n\to \mathrm{\infty }}{lim sup}\left(\parallel \left(\gamma I+\left(1-\gamma \right)S\right){z}_{n+1}-\left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}\parallel -\parallel {x}_{n+1}-{x}_{n}\parallel \right)\le 0.$
This together with Lemma 2.4 implies that
$\underset{n\to \mathrm{\infty }}{lim}\parallel \left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}-{x}_{n}\parallel =0.$
(3.6)
Consequently, we obtain
$\underset{n\to \mathrm{\infty }}{lim}\parallel {x}_{n+1}-{x}_{n}\parallel =\underset{n\to \mathrm{\infty }}{lim}\left(1-{\beta }_{n}\right)\parallel \left(\gamma I+\left(1-\gamma \right)S\right){z}_{n}-{x}_{n}\parallel =0.$
From (3.1) and (3.2), we have
$\begin{array}{rcl}{\parallel {x}_{n+1}-z\parallel }^{2}& \le & \left(1-{\beta }_{n}\right){\parallel \left(\gamma I+\left(1-\gamma \right)S\right){T}_{{\lambda }_{n}}\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}\right)-z\parallel }^{2}\\ +{\beta }_{n}{\parallel {x}_{n}-z\parallel }^{2}\\ \le & \left(1-{\beta }_{n}\right)\left\{\left(1-{\alpha }_{n}\right)\left({\parallel {x}_{n}-z\parallel }^{2}+\frac{{\lambda }_{n}}{{\left(1-{\alpha }_{n}\right)}^{2}}\left({\lambda }_{n}-2\left(1-{\alpha }_{n}\right)\alpha \right){\parallel A{x}_{n}-Az\parallel }^{2}\right)\\ +{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\right\}+{\beta }_{n}{\parallel {x}_{n}-z\parallel }^{2}\\ =& \left(1-\left(1-{\beta }_{n}\right){\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+\frac{\left(1-{\beta }_{n}\right){\lambda }_{n}}{1-{\alpha }_{n}}\left({\lambda }_{n}-2\left(1-{\alpha }_{n}\right)\alpha \right){\parallel A{x}_{n}-Az\parallel }^{2}\\ +\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ \le & {\parallel {x}_{n}-z\parallel }^{2}+\frac{\left(1-{\beta }_{n}\right){\lambda }_{n}}{1-{\alpha }_{n}}\left({\lambda }_{n}-2\left(1-{\alpha }_{n}\right)\alpha \right){\parallel A{x}_{n}-Az\parallel }^{2}\\ +\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}.\end{array}$
Then we obtain
$\begin{array}{c}\frac{\left(1-{\beta }_{n}\right){\lambda }_{n}}{1-{\alpha }_{n}}\left(2\left(1-{\alpha }_{n}\right)\alpha -{\lambda }_{n}\right){\parallel A{x}_{n}-Az\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\parallel {x}_{n}-z\parallel }^{2}-{\parallel {x}_{n+1}-z\parallel }^{2}+\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le \left(\parallel {x}_{n}-z\parallel -\parallel {x}_{n+1}-z\parallel \right)\parallel {x}_{n+1}-{x}_{n}\parallel +\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}.\hfill \end{array}$
Since ${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$, ${lim}_{n\to \mathrm{\infty }}\parallel {x}_{n+1}-{x}_{n}\parallel =0$ and ${lim inf}_{n\to \mathrm{\infty }}\frac{\left(1-{\beta }_{n}\right){\lambda }_{n}}{1-{\alpha }_{n}}\left(2\left(1-{\alpha }_{n}\right)\alpha -{\lambda }_{n}\right)>0$, we have
$\underset{n\to \mathrm{\infty }}{lim}\parallel A{x}_{n}-Az\parallel =0.$
(3.7)
Next, we show $\parallel {x}_{n}-{z}_{n}\parallel =\parallel {x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \to 0$. By using the firm nonexpansivity of ${T}_{{\lambda }_{n}}$, we have
$\begin{array}{rcl}{\parallel {T}_{{\lambda }_{n}}{y}_{n}-z\parallel }^{2}& =& {\parallel {T}_{{\lambda }_{n}}{y}_{n}-{T}_{{\lambda }_{n}}\left(z-{\lambda }_{n}Az\right)\parallel }^{2}\\ \le & 〈{y}_{n}-\left(z-{\lambda }_{n}Az\right),{T}_{{\lambda }_{n}}{y}_{n}-z〉\\ =& \frac{1}{2}\left({\parallel {y}_{n}-\left(z-{\lambda }_{n}Az\right)\parallel }^{2}+{\parallel {T}_{{\lambda }_{n}}{y}_{n}-z\parallel }^{2}\\ -{\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}\left(A{x}_{n}-{\lambda }_{n}Az\right)-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\right).\end{array}$
We note that
${\parallel {y}_{n}-\left(z-{\lambda }_{n}Az\right)\parallel }^{2}\le \left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}.$
Thus,
$\begin{array}{rcl}{\parallel {T}_{{\lambda }_{n}}{y}_{n}-z\parallel }^{2}& \le & \frac{1}{2}\left(\left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}+{\parallel {T}_{{\lambda }_{n}}{y}_{n}-z\parallel }^{2}\\ -{\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}-{\lambda }_{n}\left(A{x}_{n}-{\lambda }_{n}Az\right)\parallel }^{2}\right).\end{array}$
That is,
$\begin{array}{rcl}{\parallel {T}_{{\lambda }_{n}}{y}_{n}-z\parallel }^{2}& \le & \left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ -{\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}-{\lambda }_{n}\left(A{x}_{n}-{\lambda }_{n}Az\right)\parallel }^{2}\\ =& \left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}-{\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\\ +2{\lambda }_{n}〈{\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n},A{x}_{n}-Az〉-{\lambda }_{n}^{2}{\parallel A{x}_{n}-Az\parallel }^{2}\\ \le & \left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+{\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}-{\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\\ +2{\lambda }_{n}\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \parallel A{x}_{n}-Az\parallel .\end{array}$
It follows that
$\begin{array}{rcl}{\parallel {x}_{n+1}-z\parallel }^{2}& \le & {\beta }_{n}{\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right)\left(1-{\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ -\left(1-{\beta }_{n}\right){\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\\ +2{\lambda }_{n}\left(1-{\beta }_{n}\right)\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \parallel A{x}_{n}-Az\parallel \\ =& \left(1-\left(1-{\beta }_{n}\right){\alpha }_{n}\right){\parallel {x}_{n}-z\parallel }^{2}+\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\\ -\left(1-{\beta }_{n}\right){\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\\ +2{\lambda }_{n}\left(1-{\beta }_{n}\right)\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \parallel A{x}_{n}-Az\parallel .\end{array}$
Hence,
$\begin{array}{c}\left(1-{\beta }_{n}\right){\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\parallel {x}_{n}-z\parallel }^{2}-{\parallel {x}_{n+1}-z\parallel }^{2}-\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {x}_{n}-z\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}+2{\lambda }_{n}\left(1-{\beta }_{n}\right)\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \parallel A{x}_{n}-Az\parallel \hfill \\ \phantom{\rule{1em}{0ex}}\le \left(\parallel {x}_{n}-z\parallel +\parallel {x}_{n+1}-z\parallel \right)\parallel {x}_{n+1}-{x}_{n}\parallel +\left(1-{\beta }_{n}\right){\alpha }_{n}{\parallel {u}_{n}-z\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+2{\lambda }_{n}\left(1-{\beta }_{n}\right)\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel \parallel A{x}_{n}-Az\parallel .\hfill \end{array}$
Since ${lim sup}_{n\to \mathrm{\infty }}{\beta }_{n}<1$, $\parallel {x}_{n+1}-{x}_{n}\parallel \to 0$, ${\alpha }_{n}\to 0$ and $\parallel A{x}_{n}-Az\parallel \to 0$, we deduce
$\underset{n\to \mathrm{\infty }}{lim}\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel =0.$
This implies that
$\underset{n\to \mathrm{\infty }}{lim}\parallel {x}_{n}-{z}_{n}\parallel =\parallel {x}_{n}-{T}_{{\lambda }_{n}}{y}_{n}\parallel =0.$
(3.8)

Put $\stackrel{˜}{x}={Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(u\right)$. We will finally show that ${x}_{n}\to \stackrel{˜}{x}$.

Setting ${v}_{n}={x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}\left(A{x}_{n}-A\stackrel{˜}{x}\right)$ for all n. Taking $z=\stackrel{˜}{x}$ in (3.7) to get $\parallel A{x}_{n}-A\stackrel{˜}{x}\parallel \to 0$. First, we prove ${lim sup}_{n\to \mathrm{\infty }}〈u-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉\le 0$. We take a subsequence $\left\{{v}_{{n}_{i}}\right\}$ of $\left\{{v}_{n}\right\}$ such that
$\underset{n\to \mathrm{\infty }}{lim sup}〈u-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉=\underset{i\to \mathrm{\infty }}{lim}〈u-\stackrel{˜}{x},{v}_{{n}_{i}}-\stackrel{˜}{x}〉.$
It is clear that $\left\{{v}_{{n}_{i}}\right\}$ is bounded due to the boundedness of $\left\{{x}_{n}\right\}$ and $\parallel A{x}_{n}-A\stackrel{˜}{x}\parallel \to 0$. Then there exists a subsequence $\left\{{v}_{{n}_{{i}_{j}}}\right\}$ of $\left\{{v}_{{n}_{i}}\right\}$ which converges weakly to some point $w\in C$. Hence, $\left\{{x}_{{n}_{{i}_{j}}}\right\}$ also converges weakly to w. At the same time, from (3.6) and (3.8), we have
$\underset{j\to \mathrm{\infty }}{lim}\parallel {x}_{{n}_{{i}_{j}}}-\left(\gamma I+\left(1-\gamma \right)S\right){x}_{{n}_{{i}_{j}}}\parallel =0.$
(3.9)

By the demi-closedness principle (see Lemma 2.6) and (3.9), we deduce $w\in F\left(S\right)$.

Further, we show that w is also in MEP. From (3.1), we have
$F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge 0.$
From (H2), we have
$〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge F\left(y,{z}_{n}\right).$
(3.10)
Put ${x}_{t}=ty+\left(1-t\right)w$ for all $t\in \left(0,1-\frac{\lambda }{2\alpha }\right)$ and $y\in C$. Then we have ${x}_{t}\in C$. So, from (3.10), we have
$\begin{array}{rcl}〈{x}_{t}-{z}_{n},A{x}_{t}〉& \ge & 〈{x}_{t}-{z}_{n},A{x}_{t}〉-〈{x}_{t}-{z}_{n},A{x}_{n}〉\\ -\frac{1}{{\lambda }_{n}}〈{x}_{t}-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉+F\left({x}_{t},{z}_{n}\right)\\ =& 〈{x}_{t}-{z}_{n},A{x}_{t}-A{z}_{n}〉+〈{x}_{t}-{z}_{n},A{z}_{n}-A{x}_{n}〉\\ -\frac{1}{{\lambda }_{n}}〈{x}_{t}-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉+F\left({x}_{t},{z}_{n}\right).\end{array}$
Since $\parallel {z}_{n}-{x}_{n}\parallel \to 0$, we have $\parallel A{z}_{n}-A{x}_{n}\parallel \to 0$. Further, from monotonicity of A, we have $〈{x}_{t}-{z}_{n},A{x}_{t}-A{z}_{n}〉\ge 0$. So, from (H4), we have
(3.11)
From (H1), (H4) and (3.11), we also have
$\begin{array}{rcl}0& =& F\left({x}_{t},{x}_{t}\right)\\ \le & tF\left({x}_{t},y\right)+\left(1-t\right)F\left({x}_{t},w\right)\\ \le & tF\left({x}_{t},y\right)+\left(1-t\right)〈{x}_{t}-w,A{x}_{t}〉\\ =& tF\left({x}_{t},y\right)+\left(1-t\right)t〈y-w,A{x}_{t}〉\end{array}$
and hence
$0\le F\left({x}_{t},y\right)+\left(1-t\right)〈y-w,A{x}_{t}〉.$
Letting $t\to 0$, we have, for each $y\in C$,
$0\le F\left(w,y\right)+〈y-w,Aw〉.$
This implies $w\in \mathit{MEP}$. Hence, we have $w\in F\left(S\right)\cap \mathit{MEP}$. This implies that
$\underset{n\to \mathrm{\infty }}{lim sup}〈u-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉=\underset{j\to \mathrm{\infty }}{lim}〈u-\stackrel{˜}{x},{v}_{{n}_{{i}_{j}}}-\stackrel{˜}{x}〉=〈u-\stackrel{˜}{x},w-\stackrel{˜}{x}〉.$
Note that $\stackrel{˜}{x}={Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(u\right)$. Then $〈u-\stackrel{˜}{x},w-\stackrel{˜}{x}〉\le 0$, $w\in F\left(S\right)\cap \mathit{MEP}$. Therefore,
$\underset{n\to \mathrm{\infty }}{lim sup}〈u-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉\le 0.$
Since ${u}_{n}\to u$, we have
$\underset{n\to \mathrm{\infty }}{lim sup}〈{u}_{n}-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉\le 0.$
From (3.1), we have
$\begin{array}{c}{\parallel {x}_{n+1}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel \left(\gamma I+\left(1-\gamma \right)S\right){T}_{{\lambda }_{n}}{y}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel {T}_{{\lambda }_{n}}{y}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}={\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel {T}_{{\lambda }_{n}}{y}_{n}-{T}_{{\lambda }_{n}}\left(\stackrel{˜}{x}-{\lambda }_{n}A\stackrel{˜}{x}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel {y}_{n}-\left(\stackrel{˜}{x}-{\lambda }_{n}A\stackrel{˜}{x}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}={\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right){\parallel {\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}-{\lambda }_{n}A{x}_{n}-\left(\stackrel{˜}{x}-{\lambda }_{n}A\stackrel{˜}{x}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}=\left(1-{\beta }_{n}\right){\parallel \left(1-{\alpha }_{n}\right)\left(\left({x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A{x}_{n}\right)-\left(\stackrel{˜}{x}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A\stackrel{˜}{x}\right)\right)+{\alpha }_{n}\left({u}_{n}-\stackrel{˜}{x}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+{\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}=\left(1-{\beta }_{n}\right)\left({\left(1-{\alpha }_{n}\right)}^{2}{\parallel \left({x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A{x}_{n}\right)-\left(\stackrel{˜}{x}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A\stackrel{˜}{x}\right)\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+2{\alpha }_{n}\left(1-{\alpha }_{n}\right)〈{u}_{n}-\stackrel{˜}{x},\left({x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A{x}_{n}\right)-\left(\stackrel{˜}{x}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}A\stackrel{˜}{x}\right)〉\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+{\alpha }_{n}^{2}{\parallel {u}_{n}-\stackrel{˜}{x}\parallel }^{2}\right)+{\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\le {\beta }_{n}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}+\left(1-{\beta }_{n}\right)\left({\left(1-{\alpha }_{n}\right)}^{2}{\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+2{\alpha }_{n}\left(1-{\alpha }_{n}\right)〈{u}_{n}-\stackrel{˜}{x},{x}_{n}-\frac{{\lambda }_{n}}{1-{\alpha }_{n}}\left(A{x}_{n}-A\stackrel{˜}{x}\right)-\stackrel{˜}{x}〉+{\alpha }_{n}^{2}{\parallel {u}_{n}-\stackrel{˜}{x}\parallel }^{2}\right)\hfill \\ \phantom{\rule{1em}{0ex}}\le \left(1-\left(1-{\beta }_{n}\right){\alpha }_{n}\right){\parallel {x}_{n}-\stackrel{˜}{x}\parallel }^{2}\hfill \\ \phantom{\rule{1em}{0ex}}\phantom{\rule{1em}{0ex}}+\left(1-{\beta }_{n}\right){\alpha }_{n}\left\{2\left(1-{\alpha }_{n}\right)〈{u}_{n}-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉+{\alpha }_{n}{\parallel {u}_{n}-\stackrel{˜}{x}\parallel }^{2}\right\}.\hfill \end{array}$

It is clear that ${\sum }_{n=1}^{\mathrm{\infty }}\left(1-{\beta }_{n}\right){\alpha }_{n}=\mathrm{\infty }$ and ${lim sup}_{n\to \mathrm{\infty }}\left(2\left(1-{\alpha }_{n}\right)〈{u}_{n}-\stackrel{˜}{x},{v}_{n}-\stackrel{˜}{x}〉+{\alpha }_{n}{\parallel {u}_{n}-\stackrel{˜}{x}\parallel }^{2}\right)\le 0$. We can therefore apply Lemma 2.7 to conclude that ${x}_{n}\to \stackrel{˜}{x}$. This completes the proof. □

Corollary 3.2 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $A:C\to H$ be an α-inverse-strongly monotone mapping and let $S:C\to C$ be a nonexpansive mapping. Suppose that $F\left(S\right)\cap \mathit{MEP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n}\hfill \end{array}$
(3.12)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,2\alpha \right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r1)

${lim}_{n\to \mathrm{\infty }}{u}_{n}=u$ for some $u\in H$;

2. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

3. (r3)

$0 and $\gamma \in \left(0,1\right)$;

4. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,2\alpha \right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.12) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(u\right)$.

Corollary 3.3 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $S:C\to C$ be a κ-strictly pseudo-contractive mapping. Suppose that $F\left(S\right)\cap \mathit{EP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n}\hfill \end{array}$
(3.13)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,1\right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r1)

${lim}_{n\to \mathrm{\infty }}{u}_{n}=u$ for some $u\in H$;

2. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

3. (r3)

$0 and $\gamma \in \left[\kappa ,1\right)$;

4. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,1\right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.13) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{EP}}\left(u\right)$.

Corollary 3.4 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $S:C\to C$ be a nonexpansive mapping. Suppose that $F\left(S\right)\cap \mathit{EP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left({\alpha }_{n}{u}_{n}+\left(1-{\alpha }_{n}\right){x}_{n}\right)〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n}\hfill \end{array}$
(3.14)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,1\right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r1)

${lim}_{n\to \mathrm{\infty }}{u}_{n}=u$ for some $u\in H$;

2. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

3. (r3)

$0 and $\gamma \in \left(0,1\right)$;

4. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,1\right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.14) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{EP}}\left(u\right)$.

Corollary 3.5 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $A:C\to H$ be an α-inverse-strongly monotone mapping and let $S:C\to C$ be a κ-strictly pseudo-contractive mapping. Suppose that $F\left(S\right)\cap \mathit{MEP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left(1-{\alpha }_{n}\right){x}_{n}〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n}\hfill \end{array}$
(3.15)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,2\alpha \right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

2. (r3)

$0 and $\gamma \in \left[\kappa ,1\right)$;

3. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,2\alpha \right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.15) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{MEP}}\left(0\right)$, which is the minimum norm element in $F\left(S\right)\cap \mathit{MEP}$.

Corollary 3.6 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $S:C\to C$ be a κ-strictly pseudo-contractive mapping. Suppose that $F\left(S\right)\cap \mathit{EP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left(1-{\alpha }_{n}\right){x}_{n}〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right)\gamma {z}_{n}+\left(1-{\beta }_{n}\right)\left(1-\gamma \right)S{z}_{n}\hfill \end{array}$
(3.16)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,1\right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

2. (r3)

$0 and $\gamma \in \left[\kappa ,1\right)$;

3. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,1\right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.16) converges strongly to ${Proj}_{F\left(S\right)\cap \mathit{EP}}\left(0\right)$, which is the minimum norm element in $F\left(S\right)\cap \mathit{EP}$.

Corollary 3.7 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Let $A:C\to H$ be an α-inverse-strongly monotone mapping. Suppose that $\mathit{MEP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+〈A{x}_{n},y-{z}_{n}〉+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left(1-{\alpha }_{n}\right){x}_{n}〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right){z}_{n}\hfill \end{array}$
(3.17)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,2\alpha \right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

2. (r3)

$0;

3. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,2\alpha \right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.17) converges strongly to ${Proj}_{\mathit{MEP}}\left(0\right)$, which is the minimum norm element in MEP.

Corollary 3.8 Let C be a nonempty closed convex subset of a real Hilbert space H and let $F:C×C\to R$ be a bifunction satisfying conditions (H1)-(H4). Suppose $\mathit{EP}\ne \mathrm{\varnothing }$. Let ${x}_{0}\in C$, $\left\{{z}_{n}\right\}$ and $\left\{{x}_{n}\right\}$ be sequences in C generated by
$\left\{\begin{array}{c}F\left({z}_{n},y\right)+\frac{1}{{\lambda }_{n}}〈y-{z}_{n},{z}_{n}-\left(1-{\alpha }_{n}\right){x}_{n}〉\ge 0,\phantom{\rule{1em}{0ex}}\mathrm{\forall }y\in C,\hfill \\ {x}_{n+1}={\beta }_{n}{x}_{n}+\left(1-{\beta }_{n}\right){z}_{n}\hfill \end{array}$
(3.18)
for all $n\ge 0$, where $\left\{{\lambda }_{n}\right\}\subset \left(0,1\right)$, $\left\{{\alpha }_{n}\right\}\subset \left(0,1\right)$ and $\left\{{\beta }_{n}\right\}\subset \left(0,1\right)$ satisfy
1. (r2)

${lim}_{n\to \mathrm{\infty }}{\alpha }_{n}=0$ and ${\sum }_{n=1}^{\mathrm{\infty }}{\alpha }_{n}=\mathrm{\infty }$;

2. (r3)

$0;

3. (r4)

$a\left(1-{\alpha }_{n}\right)\le {\lambda }_{n}\le b\left(1-{\alpha }_{n}\right)$, where $\left[a,b\right]\subset \left(0,1\right)$ and ${lim}_{n\to \mathrm{\infty }}\left({\lambda }_{n+1}-{\lambda }_{n}\right)=0$.

Then $\left\{{x}_{n}\right\}$ generated by (3.18) converges strongly to ${Proj}_{\mathit{EP}}\left(0\right)$, which is the minimum norm element in EP.

Authors’ Affiliations

(1)
Department of Mathematics, Tianjin Polytechnic University, Tianjin, 300387, China
(2)
Department of Information Management, Cheng Shiu University, Kaohsiung, 833, Taiwan
(3)
Department of Mathematics and the RINS, Gyeongsang National University, Jinju, 660-701, Korea

References

1. Blum E, Oettli W: From optimization and variational inequalities to equilibrium problems. Math. Stud. 1994, 63: 123–145.
2. Ceng LC, Al-Homidan S, Ansari QH, Yao JC: An iterative scheme for equilibrium problems and fixed point problems of strict pseudo-contraction mappings. J. Comput. Appl. Math. 2009, 223: 967–974. 10.1016/j.cam.2008.03.032
3. Ceng LC, Schaible S, Yao JC: Implicit iteration scheme with perturbed mapping for equilibrium problems and fixed point problems of finitely many nonexpansive mappings. J. Optim. Theory Appl. 2008, 139: 403–418. 10.1007/s10957-008-9361-y
4. Chuang CS, Lin LJ, Takahashi W: Halpern’s type iterations with perturbations in Hilbert spaces: equilibrium solutions and fixed points. J. Glob. Optim. 2013. 10.1007/s10898-012-9911-6Google Scholar
5. Colao V, Acedo GL, Marino G: An implicit method for finding common solutions of variational inequalities and systems of equilibrium problems and fixed points of infinite family of nonexpansive mappings. Nonlinear Anal. 2009, 71: 2708–2715. 10.1016/j.na.2009.01.115
6. Colao V, Marino G, Xu HK: An iterative method for finding common solutions of equilibrium and fixed point problems. J. Math. Anal. Appl. 2008, 344: 340–352. 10.1016/j.jmaa.2008.02.041
7. Combettes PL, Hirstoaga A: Equilibrium programming in Hilbert spaces. J. Nonlinear Convex Anal. 2005, 6: 117–136.
8. Konnov IV, Schaible S, Yao JC: Combined relaxation method for mixed equilibrium problems. J. Optim. Theory Appl. 2005, 126: 309–322. 10.1007/s10957-005-4716-0
9. Moudafi A: Weak convergence theorems for nonexpansive mappings and equilibrium problems. J. Nonlinear Convex Anal. 2008, 9: 37–43.
10. Moudafi A, Théra M: Proximal and dynamical approaches to equilibrium problems. 477. In Lecture Notes in Economics and Mathematical Systems. Springer, Berlin; 1999:187–201.Google Scholar
11. Peng JW, Yao JC: A new hybrid-extragradient method for generalized mixed equilibrium problems, fixed point problems and variational inequality problems. Taiwan. J. Math. 2008, 12: 1401–1432.
12. Plubtieng S, Punpaeng R: A general iterative method for equilibrium problems and fixed point problems in Hilbert spaces. J. Math. Anal. Appl. 2007, 336: 455–469. 10.1016/j.jmaa.2007.02.044
13. Qin X, Cho SY, Kang SM: Some results on generalized equilibrium problems involving a family of nonexpansive mappings. Appl. Math. Comput. 2010, 217: 3113–3126. 10.1016/j.amc.2010.08.043
14. Qin X, Cho YJ, Kang SM: Viscosity approximation methods for generalized equilibrium problems and fixed point problems with applications. Nonlinear Anal. 2010, 72: 99–112. 10.1016/j.na.2009.06.042
15. Takahashi S, Takahashi W: Strong convergence theorem for a generalized equilibrium problem and a nonexpansive mapping in a Hilbert space. Nonlinear Anal. 2008, 69: 1025–1033. 10.1016/j.na.2008.02.042
16. Xu HK: An iterative approach to quadratic optimization. J. Optim. Theory Appl. 2003, 116: 659–678. 10.1023/A:1023073621589
17. Yao Y, Liou YC: Composite algorithms for minimization over the solutions of equilibrium problems and fixed point problems. Abstr. Appl. Anal. 2010., 2010: Article ID 763506Google Scholar
18. Yao Y, Liou YC, Yao JC: Convergence theorem for equilibrium problems and fixed point problems of infinite family of nonexpansive mappings. Fixed Point Theory Appl. 2007., 2007: Article ID 64363Google Scholar
19. Yao Y, Shahzad N: New methods with perturbations for non-expansive mappings in Hilbert spaces. Fixed Point Theory Appl. 2011., 2011: Article ID 79Google Scholar
20. Zegeye H, Ofoedu EU, Shahzad N: Convergence theorems for equilibrium problem, variational inequality problem and countably infinite relatively quasi-nonexpansive mappings. Appl. Math. Comput. 2010, 216: 3439–3449. 10.1016/j.amc.2010.02.054
21. Zegeye H, Shahzad N: A hybrid scheme for finite families of equilibrium, variational inequality and fixed point problems. Nonlinear Anal. 2011, 74: 263–272. 10.1016/j.na.2010.08.040
22. Zhang SS, Joseph HWL, Chan CK: Algorithms of common solutions for quasi variational inclusion and fixed point problems. Appl. Math. Mech. 2008, 29: 571–581. 10.1007/s10483-008-0502-y
23. Suzuki T: Strong convergence theorems for infinite families of nonexpansive mappings in general Banach spaces. Fixed Point Theory Appl. 2005, 2005: 103–123.
24. Zhou H: Convergence theorems of fixed points for λ -strict pseudo-contractions in Hilbert spaces. Nonlinear Anal. 2008, 69: 456–462. 10.1016/j.na.2007.05.032
25. Marino C, Xu HK: Weak and strong convergence theorems for strict pseudocontractions in Hilbert spaces. J. Math. Anal. Appl. 2007, 329: 336–349. 10.1016/j.jmaa.2006.06.055